Enhanced Mainlobe Jamming Suppression in Distributed Array Radar via Joint Optimization of Radar Positions and Subpulse Frequencies - Weiming Pu; Kewei Feng; Xiaoping Wang; Zhennan Liang; Xinliang Chen; Quanhua Liu (Remote Sensing, 2025)
This study presents a joint optimization framework for radar positions and subpulse carrier frequencies to address mainlobe jamming suppression in a distributed array radar system with one main and multiple auxiliary radars. Accounting for gain and aperture differences between the main and auxiliary radars, the grating lobe effect on jamming suppression performance is analyzed. Unlike conventional sparse array design approaches, this work introduces an architecture leveraging subpulses at distinct carrier frequencies to enhance grating lobe suppression and jamming suppression. A specific joint optimization method for radar positions and subpulse frequencies is then established. With jamming suppression performance as the objective function, the method first maps the variations induced by a range of candidate frequencies onto a single representative frequency point. This mapping enables efficient optimization of radar positions across the designated frequency band. Subsequently, a sequential scheme selects specific carrier frequencies for the subpulses. In practical anti-jamming operations, the optimal frequency for the current scenario is determined by analyzing the suppression results from these subpulses. The main radar then transmits pulses at this optimal frequency, thereby reducing both system complexity and pulse accumulation difficulty. Simulation results demonstrate that the proposed method achieves a reduction of over 3 dB in grating lobe suppression compared to conventional sparse array design methods, while enhancing the output signal-to-jamming and noise ratio by nearly 3 dB after jamming suppression.